The Connection Between Professional Sporting Events, Holidays and Domestic Violence in Calgary, Alberta - Sophia Boutilier; Ali Jadidzadeh; Elena Esina; Lana Wells; Ron Kneebone
There are some days in Calgary, Alta when domestic violence is more likely to happen than other days. There is a statistically significant connection between higher rates of domestic violence and certain Calgary Stampeders’ football games as well as the arrival of the Calgary Stampede. During the 10-day-long Calgary Stampede, domestic violence calls on the seventh, ninth and tenth day of Stampede, were up 15 per cent compared to an average day. Weekends and summer months were also generally associated with the highest rates of domestic violence reports in Calgary. When it came to Calgary Stampeders’ football games, calls were higher only when the Stampeders faced off against the rival Edmonton Eskimos – with a 15 per cent increase in domestic violence reports. Grey Cup games in which Calgary played were associated with a 40 per cent increase in reports of domestic violence. However, games played by the Calgary Flames seemed to have no relationship to domestic violence calls, even those against the rival Edmonton team. Also, New Year’s Day appears to be associated with a significant spike in domestic violence, going by a four-year count of phone calls reporting domestic violence to both police and a local help line for those experiencing domestic and sexual abuse. There are also increases in calls associated with Good Friday, Easter, Canada Day, Labour Day, Valentine’s Day and Halloween. Meanwhile, the 2013 catastrophic floods in Calgary resulted in an increase in reports of domestic violence to police and the Connect help line, averaging an additional 6.6 reported incidents of domestic violence per day during the flood, 14 per cent higher than average.